(untitled) (European Journal of Pure and Applied Mathematics, 2024)
A subset A of a bitopological space (X,τ_1,τ_2) is called (i,j)-ψgs-closed set if (i,j)-ψ cl(A)U whenever AU, U is (i,j)-semi-open in (X,τ_1,τ_2). In this work, the properties of this set are considered to investigate the concepts of ψ gs-functions in bitopological spaces. Specifically, this study establishes some properties and provide characterizations of ψ gs-open and ψ gs-closed functions, ψ gs-continuous functions, and ψ gs-irresolute functions in bitopological spaces.